PTEN attenuates PIP(3)/Akt signaling in the cochlea of the aging CBA/J mouse - Sha, Su-Hua (2009)
We have previously reported the activation of cell death pathways in the sensory cells of the aging cochlea. Here we investigate age-associated changes in survival mechanisms focusing on phosphatidylinositol 3,4,5-trisphosphate (PIP(3))/Akt signaling. The animal model is the CBA/J mouse of 18 months of age prior to the onset of major functional loss (ABR thresholds, 26 8 dB SPL) which is compared to young animals of 3 months of age (ABR thresholds, 19 7 dB SPL). Immunostaining on cochlear cryosections revealed a wide-spread distribution of PIP(3) in the cochlea which was markedly attenuated in old animals in inner and outer hair cells, Deiters cells and pillar cells. Protein levels of the lipid phosphatase PTEN which regulates PIP(3) increased in those cells with aging while its mRNA did not, suggesting an age-related reduction of PTEN degradation. Furthermore, staining intensity of phosphorylated PTEN (ser380) and its nuclear localization increased. Consistent with a reduction of PIP(3), the phosphorylation of the downstream target Akt at threonine 308 significantly decreased in outer hair cells. The results suggest a decline of the survival capacity of aging outer hair cells due to a decrease in PIP(3)/Akt signaling caused by an increase of PTEN.